2023
DOI: 10.1002/adma.202307756
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrons Sequentially Regulate Antibacterial Activity and Osseointegration of Titanium Implants

Yufei Tang,
Kai Wang,
Bingfeng Wu
et al.

Abstract: Titanium implants are widely used in the biological field, however, implantation occasionally fails due to infection from the microbes during the surgery or poor osseointegration after the surgery. To solve the problem, we have designed an intelligent functional surface on the titanium implant that can sequentially eradicate bacteria biofilm at the initial period of post‐surgery time and promote osseointegration at the late period of post‐surgery time. Such surface can be excited by near infrared light (NIR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…It suggested that the released Sr from Sr/TiO 2 and Zn–Sr/TiO 2 was able to promote the osteogenic activity by modulating macrophage M2 activation. Based on in vitro experiment results, the mouse femoral implantation model was developed as reported, 55 to further confirm the in vivo effect of Zn–Sr/TiO 2 (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that the released Sr from Sr/TiO 2 and Zn–Sr/TiO 2 was able to promote the osteogenic activity by modulating macrophage M2 activation. Based on in vitro experiment results, the mouse femoral implantation model was developed as reported, 55 to further confirm the in vivo effect of Zn–Sr/TiO 2 (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…The precise coupling and sequential combination of antibacterial and anti-inflammatory properties with cell proliferation promotion, according to the microenvironment of different tissue repair phases, is of great demand for implantable tissue repair materials but remains challenging [ [1] , [2] , [3] , [4] , [5] ]. The titanium anastomotic staple commonly used in gastrointestinal surgery, can be considered as an ideal model to explore the biological applications of multifunctional implantable materials [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%